BOWEL CANCER SCREENING–ARE THE PATIENTS TRULY ASYMPTOMATIC?. (8th June 2013) - Somerville, J; Lynch, P; Rodgers, C; Jacob, G; McCrory, D
Abstract : Introduction: Bowel Cancer Screening (BCS) was launched in 2010 in Northern Ireland, with screening colonoscopy lists starting in the Northern Trust in May 2010. Screening is offered every two years to all men and women aged 60 to 71. Aims/Background: To determine the number of colorectal cancers diagnosed within the BCS programme in the Northern Trust, and of these, to identify any who were symptomatic at the time of entry to the screening programme. Method: Patients diagnosed with colorectal cancer within the BCS programme in the Northern Trust up to the end of January 2013 were identified from records kept by the Specialist Screening Practitioners. Data from endoscopy, radiology, pathology and MDM reports were then gathered for analysis, and symptomatology identified from the patient history in the pre-assessment documentation. Results: 68 patients (20 female, 48 male) have been diagnosed with colorectal cancer within the Northern Trust BCS programme. 62 of these tumours were diagnosed by colonoscopy and 6 by CT colography. Only 3 patients had evidence of distant metastases on completion of staging investigations. For 21 patients, the pre-assessment documented the recent onset of alarm symptoms – 1 iron deficiency anaemia, 4 PR bleeding, 15 changes in bowel habit and 1 faecal leakage. Only one had previously sought medical advice for these symptoms. Conclusion: The BCS programme is effective in the early detection of colorectal carcinoma. Although designed for screening asymptomatic patients, nearly a third of patients diagnosed with colorectal cancer within the programme complained of pre-existing alarm symptoms.